Sharia Management Perspective in Management Economic Business Unit of the Nurul Haramain Islamic Boarding School NW Narmada - Ermawati (Journal of Multidisciplinary Science, 2022)
This study focuses on the influence of the sharia management perspective in the management of the economic business unit management of the Nurul Haramain Islamic Boarding School NW Narmada. The approach used in this research is descriptive qualitative. The data sources of this research are primary and secondary data. Data collection techniques using interviews, observation and documentation. As for the results of this study, the management of the economic business unit at the Nurul Haramain NW Narmada Islamic Boarding School can be said to be sharia, this can be seen from HR planning not seen from educational background but good spiritual motivation, trustworthiness, and responsibility.